PERBEDAAN KUALITAS IKAN BANDENG (Chanos chanos Forsk) DURI LUNAK YANG DIPROSES MENGGUNAKAN BAHAN BAKAR KAYU DAN BRIKET ARANG - Darmawan, Adhitya Wahyu; Agustini, Tri Winarni; Riyadi, Putut Har (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Wood is the fuel used in the processing of milkfish soft thorns. Briquette charcoal is analternative fuel that can replace wood. The research was conducted to determine the effect oflong cooking using charcoal briquettes (9, 10 and 11 hours) and the firewood for 10 hours(control) to the organoleptic and nutritional quality milkfish soft thorns.The material in this research is as much as 200 kilograms of milk fish (Â±500gr/pcs), salt2%. Experimental design used was completely randomized design, comparing the differencein the length of time cooking charcoal briquettes 9, 10 and 11 hours and 10 hours firewood(control). The parameters measured were the levels of protein, fat, water, ash, andorganoleptic.The results showed that the difference in the length of time cooking (charcoalbriquettes) provides a very real difference (P<0,01) the levels of protein, fat, water and ashand organoleptic. The results of organoleptic owned milkfish duri lunak best with 9 hours ofcooking time using charcoal briquettes in the amount of 8,18< m< 8,9, while cooking usingÂ charcoal briquettes for 10 and 11 hours as well as firewood for 10 consecutive hours is :7,83<m<8,42, 7,89<m<8,24, 8,13<m< 8,51.